Implementasi Sistem ERP untuk Membantu Proses Bisnis UMKM di Indonesia - Louise Emmanuel Geraldo; Yanda Bara Kusuma (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
This journal discusses the use of Enterprise Resource Planning (ERP) systems in Small and Medium Enterprises (MSME) in Indonesia. Implementing ERP in MSME can help improve flexibility and integrate all business processes, such as inventory management, finance, production, and sales. However, implementing ERP requires careful preparation, including selecting the right vendor, optimizing internal teams, and preparing human resources. The research method used is the Participatory Action Learning System (PALS), which involves active participation from stakeholders of MSME and ERP vendors. The process of implementing ERP systems in MSME includes stages of meetings, planning, system design, education and mentoring, and using the system in business operations. The steps for implementing ERP systems in MSME include Sales Briefing Document, Function Requirement Document, User Acceptance Test, Training, and Go Live.